Bridged α-helix mimetic small molecules. Issue 88 (21st October 2019) - Lee, Yeongju; Im, Haeri; Das, Sanket; Oh, Misook; Lee, Ji Hoon; Ham, Sihyun; Lim, Hyun-Suk
Abstract : Herein, we report a strategy for generating conformationally restricted α-helix mimetic small molecules by introducing covalent bridges that limit rotation about the central axis of α-helix mimetics. Abstract : Herein, we report a strategy for generating conformationally restricted α-helix mimetic small molecules by introducing covalent bridges that limit rotation about the central axis of α-helix mimetics. We demonstrate that the bridged α-helix mimetics have enhanced binding affinity and specificity to the target protein due to the restricted conformation as well as extra interaction of the bridge with the protein surface.